The cytoprotective effects of Δ-17 fatty acid desaturase on injured HUVECs and its underlying mechanism - Xiulan Zhang; Shixin Xia; Qiqi Xu; Jiandong Huang (Elsevier, 2017)
Endothelium toxicity has been involved in early endothelial dysfunction to show the pathogenesis of multiple cardiovascular disease that shows atherosclerosis and its complications. Saturated free fatty acids are the main inducing factors of endothelial cell apoptosis and inflammatory cytokines. In humans, stearoyl-CoA desaturase 1 (SCD-1) is a restriction step to saturation to unsaturated fatty acid desaturation, which plays a beneficial role protecting endothelial cells against lipotoxicity. Δ-17 fatty acid desaturase (FAD) is a newly identified FAD which shares 55% identity at the amino acid level with SCD-1. Whether Δ-17 FAD has similar beneficial effect remains poorly understood. Oxidized low density lipoprotein (ox-LDL) was used to induce lipotoxicity in human umbilical vein endothelial cells (HUVECs) to establish a model of oxidative injury. Then HUVECs were transfected with FAD lentivirus to introduce cytoprotective effects. The alterations in cell proliferation and apoptosis, nitric oxide content, malonyldialdehyde (MDA) content, SOD enzyme content, LDH content, GSH-PX level, vascular growth factor (VEGF) expression were evaluated. Studies showed that ox-LDL-induced excess HUVEC apoptosis can be abrogated by upregulation of Δ-17 FAD. The nitric oxide content, GSH-PX content, and SOD enzyme content were increased and the activity of MDA was suppressed by upregulation of Δ-17 FAD. In addition, upregulation of Δ-17 FAD significantly increased VEGF expression. In vitro tube formation assay showed that Δ-17 FAD promoted angiogenesis to a significant degree. These results suggest that Δ-17 fatty acid desaturase may have beneficial action in the prevention of ox-LDL-induced cellular damage. Keywords: Δ-17 fatty acid desaturase, Oxidative damage, Human umbilical vein endothelial cell, Atherosclerosis